A pilot open-label trial of minocycline in patients with autism and regressive features - Pardo, Carlos A (BioMed Central, 2013)
BACKGROUND: Minocycline is a tetracycline derivative that readily crosses the blood brain barrier and appears to have beneficial effects on neuroinflammation, microglial activation and neuroprotection in a variety of neurological disorders. Both microglial activation and neuroinflammation have been reported to be associated with autism. The study was designed to evaluate the effects of minocycline treatment on markers of neuroinflammation and autism symptomatology in children with autism and a history of developmental regression. METHODS: Eleven children were enrolled in an open-label trial of six months of minocycline (1.4 mg/kg). Ten children completed the trial. Behavioral measures were collected and cerebrospinal fluid (CSF), serum and plasma were obtained before and at the end of minocycline treatment and were analyzed for markers of neuroinflammation. RESULTS: Clinical improvements were negligible. The laboratory assays demonstrated significant changes in the expression profile of the truncated form of brain derived neurotrophic factor (BDNF) (P = 0.042) and hepatic growth factor (HGF) (P = 0.028) in CSF. In serum, the ratio of the truncated BDNF form and α-2 macroglobulin (α-2 M), was also significantly lower (P = 0.028) while the mature BDNF/α-2 M ratio revealed no difference following treatment. Only the chemokine CXCL8 (IL-8) was significantly different (P = 0.047) in serum while no significant changes were observed in CSF or serum in chemokines such as CCL2 (MCP-1) or cytokines such as TNF-α, CD40L, IL-6, IFN-γ and IL-1β when pre- and post-treatment levels of these proteins were compared. No significant pre- and post-treatment changes were seen in the profiles of plasma metalloproteinases, putative targets of the effects of minocycline. CONCLUSIONS: Changes in the pre- and post-treatment profiles of BDNF in CSF and blood, HGF in CSF and CXCL8 (IL-8) in serum, suggest that minocycline may have effects in the CNS by modulating the production of neurotrophic growth factors. However, in this small group of children, no clinical improvements were observed during or after the six months of minocycline administration. TRIAL REGISTRATION: NCT00409747